LOTUS LEAF (NELUMBO NUCIFERA) EXTRACT AND ITS EFFECTS ON DYSLIPIDEMIA: A NARRATIVE REVIEW (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize current evidence on the bioactive constituents of lotus leaf (Nelumbo nucifera), particularly nuciferine and flavonoids, and its effects on dyslipidemia, fatty liver, and related metabolic markers.Methods: A narrative review was conducted using targeted searches in PubMed and reference tracking up to March 2026 with keywords related to lotus leaf, nuciferine, dyslipidemia, obesity, and fatty liver. Studies were included if they directly evaluated lotus leaf extracts or major lotus leaf compounds on lipid parameters, fat accumulation, fatty liver, or relevant biological mechanisms.Results: Preclinical evidence suggests that lotus leaf extracts may reduce total cholesterol, triglycerides, LDL-C, body fat accumulation, and hepatic fat deposition, while also improving oxidative stress, metabolic inflammation, and associated metabolic disturbances. Proposed mechanisms include inhibition of lipid- and carbohydrate-digesting enzymes, suppression of de novo lipogenesis, AMPK activation, promotion of fatty acid beta-oxidation through the PPARα/PGC1α pathway, inhibition of adipocyte differentiation, and modulation of gut microbiota. Human clinical data remain limited and currently only suggest potential improvement in body composition among overweight individuals.Conclusion: Lotus leaf is a promising herbal candidate for lipid and metabolic support; however, current evidence is insufficient to consider it an independent lipid-lowering therapy. Further high-quality clinical trials are needed to clarify its efficacy and practical role.
Keywords: lotus leaf, Nelumbo nucifera, nuciferine, dyslipidemia, fatty liver